Séries de Fourier e o Teorema de Equidistribuição de Weyl - Passos, Rokenedy Lima (2017)
This work is treated in two parts. The first is to find sufficient conditions for a function so that its Fourier series distributions become common and uniform, as well as an approach to Fejér’s Theorem, an interesting and useful result of no Fourier Series study. A second part of the application of the Fourier Series, Weyl equidistribution theorem. A problem that lies at the frontier of Dynamic Systems with a Theory of Numbers. The same refers to the distribution of irrational numbers in the range [0, 1).